A Digital Transformation Model for Traditional Markets Based on Local Wisdom to Achieve Sustainable Competitive Advantage - Gde Mahesa Satria Nugraha; Nyoman Sri Subawa (STIE Amkop Makassar, 2026)
Digital transformation in Bali's traditional markets is becoming increasingly important due to shifting tourist behaviors and the demand for more adaptive tourism services. However, the digitalization of traditional markets involves more than just the implementation of technology; it also encompasses community readiness, user acceptance, cultural preservation, and the market's ability to maintain long-term competitiveness. This study aims to analyze the digital readiness of Bali's traditional markets and its relationship with technology acceptance, digital transformation, sustainable tourism, and sustainable competitive advantage. A qualitative approach was employed, utilizing observations and interviews with market stakeholders and tourists. The analysis also identified various forms of digitalization adoption and the barriers faced by traditional markets. The findings indicate that digitalization has begun through the use of digital payments, social media, and product information provision; however, implementation remains suboptimal due to limitations regarding digital literacy, facilities, connectivity, technological understanding, and the readiness of some vendors. The Technology Acceptance Model (TAM) perspective highlights perceived usefulness and ease of use as critical factors in technology acceptance, while Digital Transformation Theory suggests that digitalization must be understood as a shift in transaction processes, marketing, service delivery, tourist interactions, and value creation. The study further demonstrates that digital readiness serves as a crucial foundation for successful digital transformation. Integrating digital readiness with local wisdom, product authenticity, community participation, and technology can strengthen the sustainable competitive advantage of Bali's traditional markets. Thus, effective digital transformation does not aim to replace the traditional character of the markets but rather to enhance competitiveness and the tourist experience while preserving Balinese cultural values. Keywords: Digital Readiness, Digital Transformation, Sustainable Competitive Advantage, Traditional Market, Sustainable Tourism.